Responsible international citizenship and China’s participation in Arctic regionalization - Kauppila Liisa; Kopra Sanna (Arctic Portal (AP), 2025)
This paper analyses the normative underpinnings of China’s participation in processes of Arctic regionalization. Building on Gareth Evans’ concept of responsible international citizenship, it argues that China’s Arctic engagement is chiefly motivated by the government’s efforts to promote the wellbeing of Chinese citizens – a state of affairs that the current regime equals with the ideal of social stability. As a responsible international citizen, China should, however, advance this “enlightened self-interest” vis-á-vis other members of the Arctic international society, that is, either internalize the established practices that organize the Arctic region or mold them in peaceful ways. In the empirical parts of the paper, we first identify three concrete aims that drive forward China’s participation in Arctic regionalization – creating wealth through more “green” growth, mitigating the effects of climate change on China, and promoting a unifying ideology. We then suggest that China has not directly violated any of the key organizing principles of the Arctic international society, but it has found distinct ways to act out these concrete goals and advance the wellbeing of its citizens. Such means include somewhat challenging the dominant interpretation of these norms and refraining from advocating stricter environmental standards.